Transcriptome-wide N6-methyladenosinem modifications analysis of chicken cecum in responding to Campylobacter jejuni inoculation - Zhao, Yanan; Wang, Yuanmei; Liu, Liying; Ren, Yanru; Liu, Long; Wang, Jiayi; Li, Xianyao (Frontiers in Immunology, 2025)
IntroductionCampylobacter jejuni (C. jejuni), a commensal food-borne pathogen, poses severe threat to human health and poultry industry. N6-methyladenosine (m6A) mRNA modification is associated with innate immunity. However, the mechanism of m6A modification in C. jejuni chicken cecum inoculation remains unclear.MethodsHere, we characterized the cecal m6A modification landscape of chicken in the C. jejuni-resistant (R) and susceptible (S) groups using methylated RNA immunoprecipitation sequencing and RNA sequencing (RNA-seq), and further conducted the in vitro C. jejuni inflammatory model based on chicken macrophage-like cell line (HD11) to elucidate the specific mechanism.ResultsIn the S group, the level of proinflammatory cytokines (IL-8, IL-1β, IL-18, TNF-α, IL-17A) and global RNA methylation were significantly decreased (P < 0.05). A total of 30,427 and 30,367 m6A peaks were identified in R and S groups, which were primarily located in 3'UTR and CDS regions. Among these, 514 differential m6A peaks (270 hypermethylated peaks and 244 hypomethylated peaks) were identified, which mainly correlated with the regulation of canonical NF-kappaB signal transduction, apoptotic signaling pathway, and MyD88-dependent toll-like receptor signaling pathway. Moreover, we identified 365 differentially expressed genes (DEGs), which were mainly associated with regulation of autophagy, and toll-like receptor 9 signaling pathway, intraciliary transport involved in cilium assembly, positive regulation of mTOR signaling, defense response to bacteria. The correlation analysis revealed that m6A methylation level correlated positively with gene expression. Further analysis identified 58 differentially methylated genes (DMGs), and mainly involved in apoptosis, autophagy, Notch signaling pathway and defense response to bacteria, which mainly enriched by DMGs including IFT74, SUSD5, WDR41, STAB2, EPG5 and FOS. Furthermore, we found that YTHDC2 could involve in regulating the apoptosis and autophagy process of HD11 cells through altering the expression of DMGs including IFT74, SUSD5, STAB2, EPG5 and FOS, which was confirmed by experiments in vitro.ConclusionThis result suggested the regulatory role of m6A methylation in chicken responds to C. jejuni inoculation. Collectively, the current study characterized the m6A modification landscape of chicken cecum and identified YTHDC2 acting key regulator responsible for C. jejuni inoculation.